2017
DOI: 10.1016/j.soard.2016.12.031
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity predicts weight loss after obesity surgery

Abstract: Impulsivity measures predict weight reduction in patients undergoing bariatric surgery. This result has implications for predicting outcomes from surgical treatments of obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 62 publications
2
24
0
Order By: Relevance
“…Five studies (Alosco et al, 2014a; Kulendran et al, 2017; Xie et al, 2017; Xu et al, 2017; Stinson et al, 2018) reported having a significantly higher percentage of males than females in their sample.…”
Section: Discussionmentioning
confidence: 99%
“…Five studies (Alosco et al, 2014a; Kulendran et al, 2017; Xie et al, 2017; Xu et al, 2017; Stinson et al, 2018) reported having a significantly higher percentage of males than females in their sample.…”
Section: Discussionmentioning
confidence: 99%
“…Suspected behavioral and emotional contributions to poor outcomes have included bingeeating disorder (11) , grazing (12) , non-adherence to taking vitamins and adequate hydration (13) , poor impulse control (14) , lack of persistence (15) , depression (16) , and possibly alcohol use disorders (see Parikh et al for a review (17) ). One purpose of pre-surgical psychological evaluations presumably is to help predict probability for success, however, evidence for predictive validity is limited.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, different domains of impulsivity had been linked to obesity development . Nevertheless, there are conflicting results in this area, and further investigation of impulsivity in patients submitted to BS and its possible relationship to WR must be done …”
Section: Discussionmentioning
confidence: 99%